Biomolecular Screening of Pimpinella anisum L. for Antioxidant and Anticholinesterase Activity in Mice Brain - Aamir Mushtaq; Fatima Habib; Rosana Manea; Rukhsana Anwar; Umar Farooq Gohar; Muhammad Zia-Ul-Haq; Mobasher Ahmad; Claudia Mihaela Gavris; Liana Chicea (Molecules, 2023)
Hundreds of the plants have been explored and evaluated for antioxidant and anti-amnesic activities, so far. This study was designed to report the biomolecules of Pimpinella anisum L. for the said activities. The aqueous extract of dried P. anisum seeds was fractionated via column chromatography and the fractions so obtained were assessed for the inhibition of acetylcholinesterase (AChE) via in vitro analysis. The fraction which best inhibited AChE was so named as the P. anisum active fraction (P.aAF). The P.aAF was then chemically analyzed via GCMS, which indicated that oxadiazole compounds were present in it. The P.aAF was then administered to albino mice to conduct the in vivo (behavioral and biochemical) studies. The results of the behavioral studies indicated the significant (p < 0.001) increase in inflexion ratio, by the number of hole-pokings through holes and time spent in a dark area by P.aAF treated mice. Biochemical studies demonstrated that the oxadiazole present in P.aAF on one hand presented a noteworthy reduction in MDA and the AChE level and on the other hand promoted the levels of CAT, SOD and GSH in mice brain. The LD50 for P.aAF was calculated as 95 mg/Kg/p.o. The findings thus supported that the antioxidant and anticholinesterase activities of P. anisum are due to its oxadiazole compounds.